Chemical composition of Thymus vulgaris L. (thyme) essential oil from the Rio de Janeiro State (Brazil) - ALEXANDRE PORTE; RONOEL L. O. GODOY (Journal of the Serbian Chemical Society, 2008)
The essential oil from fresh leaves of Thymus vulgaris L. from Rio de Janeiro State, Brazil, was isolated by hydrodistillation and analyzed through a combination of GC and GC/MS. Compounds representing 95.1 % of the oil were identified. Thirty-nine constituents were detected, of which twenty-eight were identified according to their chromatographic retention indices and mass spectra. The major constituents of the oil were thymol (44.7 %), p-cymene (18.6 %) and g-terpinene (16.5 %).